Comparative effectiveness of genotype-guided and empirical bismuth-containing quadruple therapy for Helicobacter pylori eradication: a retrospective study - Pan Wang; Mengyuan Yang; Xiaolin Zhao; Haiou Ding; Jianping Cheng (Frontiers in Pharmacology, 2026)
Objective To compare the efficacy of genotype-guided versus empirical bismuth-containing quadruple therapy (BQT) for Helicobacter pylori ( H. pylori ) eradication and to identify factors influencing treatment success. Methods This single-center retrospective study included 616 patients with H. pylori infection who received 14-day BQT. All regimens comprised bismuth potassium citrate 2.6 g, a proton pump inhibitor (PPI, esomeprazole 20 mg or ilaprazole 5 mg) or a potassium-competitive acid blocker (P-CAB, keverprazan 20 mg or tegoprazan 50 mg), and antibiotics selected from amoxicillin, clarithromycin, levofloxacin, furazolidone, tetracycline, metronidazole, or doxycycline. In the empirical group, antibiotic selection was at the physician’s discretion. In the genotype-guided group, selection was tailored to qPCR-based detection of clarithromycin and levofloxacin resistance. Eradication was confirmed by urea breath test at least 4 weeks after treatment. Results Eradication rates were significantly higher with genotype-guided therapy (90.8% vs. 81.7%; OR 2.03, 95% CI 1.23–3.36; P = 0.006). In the empirical group, P-CAB-based regimens achieved higher eradication than PPI-based regimens (87.9% vs. 76.3%; OR 2.24, 95% CI 1.38–3.58; P < 0.001), whereas the difference was not significant in the genotype-guided group (93.5% vs. 86.9%; OR 2.12, 95% CI 0.94–4.78; P = 0.070). Among patients receiving genotype-guided therapy, dual resistance to clarithromycin and levofloxacin was associated with the lowest eradication rate (82.9%), significantly lower than that in the fully susceptible group (94.1%; OR 0.30, 95% CI 0.11–0.86; P = 0.025). Current alcohol consumption was an independent risk factor for eradication failure (OR 0.39, 95% CI 0.16–0.92; P = 0.032). Conclusion Genotype-guided BQT significantly improved H. pylori eradication compared with empirical BQT. The superiority of P-CAB over PPI was most evident in the empirical setting. Dual clarithromycin and levofloxacin resistance and alcohol consumption remained key determinants of treatment failure even with genotype-guided therapy. However, the precision of estimates for single-drug resistance subgroups was limited by small sample sizes and should be interpreted cautiously.